Comparing the Left Distal Transradial Artery Access to Traditional Access Methods For Coronary Angiography: A Single-Center Experience - Saleem, Maleeha; Hamilton, Steven A; Pahuja, Karan; Hassib, Mohab; Elkhouly, Ahmed; Haseeb-ul-Rasool, Muhammad; Fox, Justin (Cardiology and Cardiovascular Medicine, 2022)
Objective: The aim of this study was to compare the effectiveness and safety of left distal transradial (LdTRA) approach in patients who had prior coronary artery bypass grafting (CABG) with conventional femoral and radial access for coronary angiography. Background: The left distal transradial approach (LdTRA) is newer vascular access for coronary angiography. We hypothesized that LdTRA is superior to traditional femoral (TFA) and traditional right radial approaches for cardiac catheterization in patients who underwent prior bypass graft surgery (CABG). Methods: We retrospectively evaluated 417 patients with prior CABG, undergoing coronary angiography at our institution between January 2018 and August 2020, to compare the type of intervention using site of access as the independent factor. We screened patients' charts using Xper IM. Analyses were performed by Statistical Product and Services Solution using Chi Square test and Pearson's correlation for categorical data and ANOVA test for nominal data, at a p value of <0.05. Predefined endpoints were time to access, procedure duration, mean length of hospital stay, fluoroscopy time and dose. Results: The mean time for femoral access was 37.68±1.19 seconds (95% CI 35.3295-40.04), for LdTRA (snuffbox access) was 36.4±5.06 seconds (95% CI=26.03-46.81), and for proximal radial access was 40.71±4.17 seconds (95% CI=31.21-50.20).Mean procedural time via femoral access was 37.68±1.97 minutes, via snuffbox access was 36.43±5.06 minutes, and via radial access was 40.71±4.17 minutes. Mean length of stay for femoral access was 1.97±0.14 days, for radial access 2.13±0.31 days and for snuffbox access 1.68±0.27 days. The fluoroscopy time for femoral access was 10.23±0.41 minutes, for snuffbox access